The Relation of Obesity and Individual Factors with Knee Osteoarthritis - Anggraini, Niken Enestasia; Hendrati, Lucia Yovita (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTOsteoarthritis represent disease at most found in the world, including in Indonesia. This disease cause pain in bone and disability at patient so disturb everyday activity. One of removed occurrenceÂ of knee OsteoarthritisÂ was obesity. Other factors like age, gender, physical activity, and habit smoke were risk factors of knee Osteoarthritis . This research was the relationship of obesitas and individuals factors with occurrence knee osteoarthritis at Surabaya Islamic Hospital. The methods of this research was an observation with case control design. Level of sampel was 64 which consist of 32 case group and 32Â control group from incomed patient to radiology unitÂ Islamic Hospital Surabaya for X-Ray photo. The dependent variable was occurence of knee osteoarthritis . The independent variables were obesity, gender, age, physical activity, habit smoke. The instrument used was a questionnaire and form BMI measurement. Data analysis used Chi-Square test with Î±=0,05 and to know oods ratio (OR)Â used statclac. The results showed significant relationship between occurence of knee osteoartritis with obesity (p=0,001,OR=7,20), age (p=0,012,OR=3,67) , gender (p=0,005,OR=4,69). For the characteristic of habit smoke (p=0,268,OR=0,56) and physical activity (p=0.919,OR=0,71) wereânt associated withÂ occurence of knee OsteoarthritisÂ at Surabaya Islamic Hospital. Â The conclusion there is relationship between obesity with knee osteoarthritisÂ at Surabaya Islamic Hospital. Risk factor knee osteoarthritis like gender and age also there were relation with occurence of knee osteoarthritis , for the risk factor of physical activity and habit smoke wereânt relation with occurence of knee osteoarthritis. Keyword : Knee osteoarthritis, obesity, individual factors